SEASONAL OCCURRENCE OF ENDOPHYTIC MYCOFLORA OF INNER BARK OF MEDICINAL PLANT ACACIA CATECHU WILLD - T. G. NAGARAJA; P. G. DEVKAR (The Bioscan, 2010)
Endophytic fungi from inner bark of medicinal plant Acacia catechu Willd were studied in different seasons during 2007-2008. A total of 32 endophytes were recorded during rainy season followed by 29 endophytes in winter season and 19 endophytes in summer season. Aspergillus niger, A. flavus, Trichoderma viridi and Penicillium sp., were found to be dominant endophytes followed by Fusarium oxysporum, Chaetomium globossum and Verticillium sp.